2020
DOI: 10.4244/eij-d-19-00507
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous left atrial appendage closure versus non-vitamin K oral anticoagulants in patients with non-valvular atrial fibrillation and high bleeding risk

Abstract: Aims: A significant number of patients with non-valvular atrial fibrillation (NVAF) are ineligible for nonvitamin K oral anticoagulants (NOACs) due to previous major bleeding or because they are at high bleeding risk (HBR). In this setting the indication for percutaneous left atrial appendage closure (LAAO) is a valuable alternative. We aimed to evaluate the efficacy and safety of NOACs versus LAAO indication in NVAF patients at HBR (HAS-BLED ≥3).Methods and results: All consecutive patients who underwent succ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
35
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(42 citation statements)
references
References 26 publications
0
35
0
Order By: Relevance
“…Long-term follow-up of the PREVAIL and PROTECT AF trials showed that the LAAO group had significantly lower cardiovascular deaths (HR: 0.59, P < 0.01), disabling/fatal stroke (HR: 0.45, P = 0.05), hemorrhagic stroke (HR: 0.20, P < 0.01) and major bleeding (HR: 0.48, P < 0.01) relative to those on warfarin (Reddy et al, 2017). The PRAGUE-17 study revealed that LAAO was noninferior to NOAC in preventing ischemic/bleeding (HR: 0.84, P = 0.004) (Godino et al, 2020). Our data suggest that in CKD patients, the incidence of stroke/TIA (2.17%) or bleeding (4.53%) is low during follow-up period, indicating that LAAO is sufficiently safe and effective.…”
Section: Efficacy and Safety During Follow-upmentioning
confidence: 99%
“…Long-term follow-up of the PREVAIL and PROTECT AF trials showed that the LAAO group had significantly lower cardiovascular deaths (HR: 0.59, P < 0.01), disabling/fatal stroke (HR: 0.45, P = 0.05), hemorrhagic stroke (HR: 0.20, P < 0.01) and major bleeding (HR: 0.48, P < 0.01) relative to those on warfarin (Reddy et al, 2017). The PRAGUE-17 study revealed that LAAO was noninferior to NOAC in preventing ischemic/bleeding (HR: 0.84, P = 0.004) (Godino et al, 2020). Our data suggest that in CKD patients, the incidence of stroke/TIA (2.17%) or bleeding (4.53%) is low during follow-up period, indicating that LAAO is sufficiently safe and effective.…”
Section: Efficacy and Safety During Follow-upmentioning
confidence: 99%
“…Procedure-related strokes occurred in 1.1% of the cases in the PROTECT AF trial and in 0.4% in the PREVAIL trial [15,16]. Godino et al report a periprocedural stroke in 6 (3.1%) of 193 left atrial appendage occlusion (LAAO) patients [17]. In the large National Cardiovascular Data Registry (NCDR) a peri-procedural ischemic stroke was apparent after 45 (0.12%) of the 38,151 LAAO procedures [18].…”
Section: Left Atrial Appendage Occlusionmentioning
confidence: 99%
“…The left atrial (LA) appendage is the main site of thrombus formation in patients with non-valvular AF. Closure of the left atrial appendage has been proposed as alternative to oral anticoagulation for stroke prophylaxis; studies have demonstrated that LAAC is as effective as warfarin and nonvitamin K oral anticoagulants in preventing strokes (3,4). LAAC in combination with AF ablation in a single procedure, might be effective in both controlling sinus rhythm and preventing stroke, without the additional risk of multiple procedures (5,6).…”
Section: Introductionmentioning
confidence: 99%